Sistem Informasi Online Pengelolaan Dana Sosial Pada Rumah Yatim Sumatera Utara - Muhammad Zulpan Batubara; Muhammad Irwan Padli Nasution (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Rumah Yatim, a National Zakat Management Institution under BAZNAS, manages various forms of donations across Indonesia through 20 branch offices. However, data management using Microsoft Excel has drawbacks, which led to the creation of an Online Social Fund Management Information System in North Sumatra using MySQL, PHP, HTML, and the Waterfall method. The system ensures transparent and systematic data management, making it easier for donors to donate online and providing real-time information on donation management. The new system has allowed Rumah Yatim to receive donations more efficiently and track them more systematically and transparently, resulting in better decision-making processes and more effective distribution of funds to those in need. The system has also helped streamline administrative tasks and reduce the time and resources required for manual data entry and report creation, leading to overall improved effectiveness and efficiency in operations.